Sulfasalzine in the management of pure axial spondyloarthritis: Need to have a relook! - Subramanian Shankar; Arun Hegde (Indian Journal of Rheumatology)
The role of sulfasalazine in pure axial spondyloarthritis (axial SpA) is claimed to be almost non-existent, due to very low-quality evidence from available literature. Guidelines recommend early institution of biologic therapy if one fails 2 NSAIDs sequentially in optimal doses over 4 weeks. As NSAIDs are effective in about 70% cases, the remaining 30% patients would require biologics within the first few weeks of onset of illness. With each passing year, a significant percentage of the remaining patients would require biologics due to NSAID failure. Relapse rates after discontinuation of TNFα inhibitors at 1-year followup is almost 100%, implying lifelong therapy with biologics. Cochrane metaanalysis reveals that ASAS 40 response (40% improvement in pain, function, and inflammation) is in the range of 25%-40% for various biologics over 24 weeks. Considering that in a country with a per Capita GDP of just Rs 1.44 lakhs/ year, where 80% of people have to meet their medical expenses out of pocket and the cheapest anti TNFs cost over Rs 2 lakhs per annum, the western guidelines are clearly impractical in Indian context. In this review article, we present a contrarian view on the use of Sulfasalazine in axial SpA. We look at the available data on Sulphasalazine with a different perspective and arrive at different conclusions. We also explore the role of other innovative strategies in the management of axial SpA and suggest alternate algorithms catering to the Indian scenario.